The Effect of Food Price Fluctuations on the Poverty Rate in Aceh Province, Indonesia - Yavishan, Muhammad; Zulham, Teuku; Suriani, Suriani (Graha Primera Saintifika, 2024)
The government continues to address poverty through various policies including food security initiatives, but the poverty rate in Aceh is still relatively high when compared to other provinces in Indonesia. Given this urgency, this study aims to estimate the short-term and long-term effects of food prices on poverty rates in Aceh using an Error Correction Model (ECM) supplemented by observations of long-term equilibrium or cointegration relationships. The secondary data used is the period 2014Q1 - 2022Q4. The estimation results show that in the short and long run, food prices have a significant effect and are positively related to the poverty rate in Aceh. The imbalance between the actual poverty rate and the desired poverty rate will be adjusted over 3.32 quarters. Therefore, the Aceh Government's measures and policies in alleviating poverty need to be revisited by consistently improving the quality of human resources, quantity, and sustainability of agricultural production.